Marital Satisfaction, Age And Alcohol Use During Pregnancy: An Empirical Study Of Pregnant Women In Uyo Metropolis, Nigeria - Effiong, James E.; Umoh, Okokon O.; Ogunleye, Adedeji J. (European Scientific Journal, ESJ, 2016)
A convenient sampling technique was used to draw a sample of 110 pregnant women reporting for antenatal clinical checks in both private and public medical facilities in Uyo, Nigeria to investigate marital satisfaction and age as predictors of alcohol use during pregnancy. Kansas Marital Satisfaction Scale was used in dichotomizing respondents into satisfied and dissatisfied pregnant women in marriage, while an item in Alcohol Use Disorder Identification Test (AUDIT) delineated our cohorts into users and non-users of alcohol. A 2x2 factorial design was adopted as regards the plan of the study while a 2-way analysis of variance was used for the analysis of data collected. Results confirmed the first hypothesis which predicted that pregnant women who are satisfied in their marriages would report less alcohol use than their dissatisfied counterparts F (1, 104) = 4.70; p < .05. Findings also confirmed our second hypothesis which stated that pregnant women who are younger would report more alcohol use than their elderly counterparts F (5, 104) = 11.833; p, <.05. Discussion of findings centered on the theories of learning which formed the nucleus of this paper and it was recommended that intervention would benefit from effective and affordable psychological counseling and treatment services for women exposed to harmful and/or hazardous alcohol use predicated by marital distress, violence, depression as well as those with limited coping skills.